The Great East Japan Earthquake: Experiences and Suggestions for Survivors with Diabetes (perspective) - Kishimoto, Miyako (Public Library of Science, 2012)
The Great East Japan Earthquake and the subsequent tsunami that occurred in the afternoon of March 11, 2011, destroyed large parts of Japan’s Tohoku district. Owing to the unfavorable living environment, many diabetic patients in the refuges lost control of their blood glucose levels, and in addition, the high-calorie food provided led to severe postprandial hyperglycemia. We recommend that diabetic patients keep personal stocks of medical supplies and the medication that they require daily, as well as records of their medication. We also recommend the creation of basic guidelines to facilitate the practical prescription of medication for diabetic patients under various conditions that may arise in the aftermath of a natural disaster.